2001
DOI: 10.1111/j.1744-6155.2001.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes of Infants Receiving Breast Milk in the NICU

Abstract: ISSUES AND PURPOSE. This study compared clinical and economic outcomes for infants who were exclusively fed breast milk and infants who were fed commercial formula. DESIGN AND METHODS. A retrospective medical record review from a regional neonatal intensive care unit (N = 80) using consultation logs from the lactation coordinator and a matched sample of formula‐fed infants. RESULTS. Neither clinical (weight gain, length of stay, days of parenteral nutrition) nor economic outcomes (direct variable costs, net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…27,29 Results from this study are congruent with those of Barton et al, 34 who found no difference in cost of care or length of stay in premature infants fed exclusively breast milk compared with those fed formula. Categorical demographic data were described using frequencies and compared between groups with chi-square analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…27,29 Results from this study are congruent with those of Barton et al, 34 who found no difference in cost of care or length of stay in premature infants fed exclusively breast milk compared with those fed formula. Categorical demographic data were described using frequencies and compared between groups with chi-square analysis.…”
Section: Discussionsupporting
confidence: 89%
“…While this percentage has previously been associated with decreased incidence of LOS, 28,22 NEC, 34 and time to achievement of full enteral feedings, 36 a higher percentage of breast milk may have had a greater impact on cost of care and length of stay. Infants in the breast milk group received at least 50% breast milk feedings.…”
Section: Study Limitationsmentioning
confidence: 97%
“…38 Another study concluded that it was difficult to demonstrate sufficient cost savings of using lactation consultants while the infant continued to reside within the NICU but that it may be the long-term clinical and economic outcomes that are affected by lactation consultant support. 39 Evidence suggests that the advantages of human milk feedings especially benefit the health of immunocompromised, premature, and high-risk infants. 40 However, along with understanding the fundamental importance of human milk feedings in newborns, we must also overcome the obstacles associated with these feedings within the NICU population.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible eventually to achieve a weight gain of 14-16 g/kg per day in hospitalized preterm infants (comparable to intrauterine weight gain), catch-up growth does not occur before the time of discharge [9,10]. Published data from similar studies showed that mean weight gain during the first 2 weeks of hospitalization is 15-16 g/day [11,12].…”
Section: Discussionmentioning
confidence: 99%